2013
DOI: 10.1177/1049909112473632
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain Management as a Barrier to Pediatric Palliative Care

Abstract: Pain is common as a presenting complaint to outpatient and emergency departments for children, yet pain management represents one of the children's largest unmet needs. A child may present with acute pain for an intermittent issue or may have acute or chronic pain in the setting of chronic illness. The mainstay of treatment for pain uses a stepwise approach for pain management, such as set up by the World Health Organization. For children with life-limiting illnesses, the Institute of Medicine guidelines recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Three theoretical studies conducted in the United States (Kang et al, 2014; Mandac & Battista, 2014; Schmidt, 2011) referred to the 2010 change in federal legislation (the Affordable Care Act), which allowed for concurrent care (cure-related and palliative) for children until the age of 21. Still, despite recommendations and growing support worldwide, an important practice gap continued to exist between valued services and those that effectively reach the family (Kassam et al, 2013; Maynard & Lynn, 2014; Thompson et al, 2013). In some of the world's most populous countries, PPC services are not readily available (Downing et al, 2015), and even within the same country there might be important differences in terms of number of staff, level of funding, and education, depending on the region or state (Feudtner et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Three theoretical studies conducted in the United States (Kang et al, 2014; Mandac & Battista, 2014; Schmidt, 2011) referred to the 2010 change in federal legislation (the Affordable Care Act), which allowed for concurrent care (cure-related and palliative) for children until the age of 21. Still, despite recommendations and growing support worldwide, an important practice gap continued to exist between valued services and those that effectively reach the family (Kassam et al, 2013; Maynard & Lynn, 2014; Thompson et al, 2013). In some of the world's most populous countries, PPC services are not readily available (Downing et al, 2015), and even within the same country there might be important differences in terms of number of staff, level of funding, and education, depending on the region or state (Feudtner et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it is estimated 40 % or more of patients' chief complaints are pain related, of which a significant proportion have a moderate to severe intensity pain rating [2][3][4]. It is also estimated that 15 % of children live with chronic pain and a large majority of pediatric ED visits involve pain [5]. In fact, stewardship of proper pain medication administration and initiation is important, as a retrospective study by Hoppe et al has suggested that patients receiving opioid prescriptions for minor to moderate pain are 1.8 times more likely to receive and fill opioid analgesic prescriptions more than 1 year out of the initial ED encounter than their counterparts who did not receive a prescription [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it is observed that the literature (6,(9)(10)(11) on the subject on the screen has focused mainly on the evaluation and management of chronic cancer pain in the child, pointing out important professional barriers in performing both processes. In this direction, the present research has originality when addressing the limiting and/or facilitating conditions that permeate the care management for the hospitalized child with chronic cancer pain, under the theoretical perspective of the dialogic principle of complexity, relying on the Grounded Theory method, considering, in this particular, not only the actions of evaluation and management of pain, but also the relational and organizational context of care.…”
Section: Introductionmentioning
confidence: 99%